Anarquismos, cristianismo e literatura social no Brasil (1890-1938) - Aquino, Gustavo Ramus de (2011)
Every religion implies the production of discourses of truth and articulates modes of subjectivities that determine the constitution of the subject. The religious discourses produce moral codes and result in types of conduct. Therefore, it is impossible to deal with religion apart from a political perspective. It has emerged within Christianism what Michel Foucault calls pastoral power. It consists in the association of the sovereign with the priest, whose role is to conduct and provide the needs for its herd. The pastoral power is a political technology that individualizes and totalizes: a governmentality device. Exposing Christianism to a political analysis is to place it within a clash between authority and freedom. In the end of the 19th Century, Liev Tolstoi developed a libertarian interpretation of Christianism, providing it a subversive behavior. The Christian practice developed by the Russian writer suggests the denial of the state based on a peaceful resistance the point of departure to what has been called Christian anarchism. Tolstoi s thought has provoked anarchist activists in Brazil, between 1890 and 1938, to develop novels with the objective of disseminating anarchist ideas. These activists have used a new literature that was emerging in Brazil: the social literature. If it was possible to bring Christianism closer to an anarchist perspective, it may well be possible to discuss the opposite process, i.e., the revolutionary discourse as production of truths acquiring the form of a pastoral